PENGARUH PRODUCT QUALITY, BRAND AWARENESS DAN PRICE DISCOUNT TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA BAKSO LAVA SITUBONDO - Fagil Ali Farel Rullah; Riska Ayu Pramesthi; Muhammad Iqbal Anshory (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The purpose of this study is to determine the effect of product quality, brand awareness, and price discount on repurchase intention through consumer satisfaction as an intervening variable at Bakso Lava Situbondo. The sampling technique used in this study is simple random sampling of 97 consumers. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The test results show that product quality has a positive and significant effect on consumer satisfaction. Brand awareness has a significant effect on consumer satisfaction. Price discount has a negative but insignificant effect on consumer satisfaction, product quality has a positive and significant effect on repurchase intention, brand awareness has a negative and insignificant effect on repurchase intention, price discount has a positive and significant effect on repurchase intention, consumer satisfaction has a positive and significant effect on repurchase intention, product quality has a positive and significant effect on repurchase intention through consumer satisfaction, brand awareness has a negative and insignificant effect on repurchase intention through consumer satisfaction, price discount has a negative and insignificant effect on repurchase intention through consumer satisfaction.